2017
DOI: 10.1080/00365521.2017.1379556
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-1 and IGF-I as markers for advanced fibrosis in NAFLD – a pilot study

Abstract: This pilot study suggests an association between serum IGFBP-1 and IGF-I levels with advanced fibrosis in NAFLD patients. IGFBP1 and IGF-1 could be of interest as future biomarkers. Similar studies in larger cohorts are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
4
32
0
1
Order By: Relevance
“…Emerging evidence suggests a critical role of apolipoproteins, including APOA4, in the pathogenesis of NAFLD Specifically, Kang et al demonstrated that over‐expression of APOA4 promotes lipid accumulation in the liver, and Qin et al reported that the level of APOA4 protein was increased in the genetically obese ( ob/ob ) mice. Furthermore, a marked upregulation of APOA4, as well as SERPINE1 and IGFBP1, has been demonstrated in patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence suggests a critical role of apolipoproteins, including APOA4, in the pathogenesis of NAFLD Specifically, Kang et al demonstrated that over‐expression of APOA4 promotes lipid accumulation in the liver, and Qin et al reported that the level of APOA4 protein was increased in the genetically obese ( ob/ob ) mice. Furthermore, a marked upregulation of APOA4, as well as SERPINE1 and IGFBP1, has been demonstrated in patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, we identified several cancer‐related over‐expressed genes, including Cscbp2 , Apoa4 , Anxa2 , Serpine1 , Igfbp1 , and Tubb2a , that were associated with chromatin‐accessible regions in NASH‐derived HCC. It has been reported that up‐regulation of these genes may have significance in the hepatocarcinogenic process, in general, and in the pathogenesis of NAFLD and NAFLD‐associated liver carcinogenesis, in particular …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This “ideal test” would help clinicians identify and follow‐up patients with NASH, predicting the response to therapy and the risk of disease progression . Many studies have identified potential biomarkers to predict disease activity for the whole spectrum of NAFLD: a) cell death and apoptosis biomarkers, including caspase‐generated CK‐18 fragment (CK‐18); b) the fibroblast growth factor 21 (FGF21); c) insulin‐like growth factor 2 (IGF‐2) and the epidermal growth factor receptor (EGFR) . These biomarkers are expected to improve the ability to stratify disease severity in NAFLD and may identify additional pathways to target for treatment .…”
Section: The Need For Reliable Biomarkersmentioning
confidence: 99%
“…9,21 In addition, there is also a need to develop and validate a simple, F I G U R E 1 Extrahepatic complications of non-alcoholic fatty liver disease (FGF21); c) insulin-like growth factor 2 (IGF-2) and the epidermal growth factor receptor (EGFR). [25][26][27][28][29] These biomarkers are expected to improve the ability to stratify disease severity in NAFLD and may identify additional pathways to target for treatment. 28 However, despite several available studies, an accurate and reproducible noninvasive method to diagnose NAFLD/NASH, which could be used for screening in the general population or for patient follow-up has still not been identified.…”
Section: The Need For Reliable Biomarkersmentioning
confidence: 99%